Social Media Marketing and Fashion Purchase Intention in Indonesia's Transitional Economy - Atrisia, Marchela Indah; Syafawi, Lely; Sari, Nurmalla (Universitas Pendidikan Indonesia, 2023)
The research set out to look at how social media marketing in the fashion business in Indonesia, a developing nation, affects consumers' propensity to make a purchase. This study surveyed 118 people in Indonesia using an online survey instrument. The proposed theoretical model was tested using Smart PLS and structural equation modeling (SEM). The bootstrapping method was used to test the hypotheses and the mediating roles of brand awareness and customer satisfaction. Despite the direct influence of social media marketing on purchase intention, brand awareness and customer satisfaction do not mediate the relationship between the two. This study contributes to the literature by shedding light on the impact of social media marketing on brand awareness, customer satisfaction, and purchase intention in transition economies, such as Indonesia. Findings from this study have practical applications because they can help marketers in a variety of contexts design social media marketing strategies that are more likely to be successful in reaching their intended audiences despite economic uncertainty.